A Translational Approach to Inclusive Development - Todorova, Marija; Marais, Kobus (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2022)
The semiotic conceptualization of translation in the area of development, and especially in inclusive development that takes into consideration marginalized and vulnerable populations, allows for an understanding of translation beyond mere linguistic translation. On the one hand, this article advances the theoretical discussion of translation in development studies. On the other hand, it also provides a diversity of contexts, both geographic and historical, in which translation plays an important role in development processes and practices. Two major themes have surfaced in the issue: (1) the distinction in the approaches to the development agenda from a North–South aid and a South–South cooperation perspective, with a special focus on China; and (2) the multidirectional and multilingual flow of knowledge and the need to preserve indigenous knowledge by preserving and translating indigenous languages.